THE WAYS OF THE FREIGHT TRAIN TRUCKS DESIGN IMPROVEMENT - Bosov, A. A.; Myamlin, S. V.; Panasenko, V. Ya.; Klymenko, I. V. (Science and Transport Progress, 2009)
In the article the analysis of factors influencing upon wear of a «wheel – rail» pair is organized and the conclusion on advisability of creation of the third kind kinematical pair in a «side girder – axle box» assembly is made .